Peculiarities of methodological approach to changing parameters of technical condition of pneumatic tires of self-propelled agricultural machines (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
The author has developed the peculiarities of the methodological approachto changing the parameters of the technical condition of pneumatic tires of self-propelled agricultural machines. The obtained analytical dependencies make it possible to establish changes in the depth of the rut, especially in over moistened soils, under the influence of the machine driver.
Keywords: tire; parameter; machine